2016
DOI: 10.1111/ina.12314
|View full text |Cite
|
Sign up to set email alerts
|

Short-range airborne transmission of expiratory droplets between two people

Abstract: The occurrence of close proximity infection for many respiratory diseases is often cited as evidence of large droplet and/or close contact transmission. We explored interpersonal exposure of exhaled droplets and droplet nuclei of two standing thermal manikins as affected by distance, humidity, ventilation, and breathing mode. Under the specific set of conditions studied, we found a substantial increase in airborne exposure to droplet nuclei exhaled by the source manikin when a susceptible manikin is within abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
286
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 250 publications
(315 citation statements)
references
References 50 publications
10
286
1
8
Order By: Relevance
“…This distance is in agreement with the threshold distance suggested in past studies10,52 when distinguishing between short-range and longrange cross-infection. There are many places where people might either stand or sit, such as hospital wards, buses, and trains.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…This distance is in agreement with the threshold distance suggested in past studies10,52 when distinguishing between short-range and longrange cross-infection. There are many places where people might either stand or sit, such as hospital wards, buses, and trains.…”
supporting
confidence: 92%
“…A few studies using thermal manikins reported the velocity of the exhaled airflow for normal breathing: 3.0 m/s (at peak) from the nose, 23 2.0-3.0 m/s (at peak) from the mouth, 24 4.74 m/s (at peak) from the mouth, 6 and 2.67 m/s (averaged) from the mouth. 10,23,32 It is important to define and use the concept of a "standard person" in studies of cross-infection when comparing the results of different studies. [26][27][28][29] The differences in exhaled airflow velocity defined and reported in past studies suggest that there may be considerable variation between different groups of people.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations